Correlation between crystallinity and mid-infrared optical absorption spectra of silicon supersaturated with sulfur. Issue 1738 (19th March 2015) - Umezu, Ikurou; Nagao, Katsuki; Nakai, Tatsuya; Naito, Muneyuki; Inada, Mitsuru; Saitoh, Tadashi; Aoki, Tamao; Sugimura, Akira
ABSTRACT: We prepared silicon hyperdoped with sulfur by ion-implantation followed by pulsed laser melting. Effects of laser fluence during pulsed laser melting and of post-annealing on the silicon hyperdoped with sulfur are investigated. The structure of hyperdoped layer changes from poly-to mono-crystal with increasing laser fluence. Interface between sulfur-implanted-layer and single-crystal substrate disappear above 1.1 J/cm 2 . The spectral intensity of mid-infrared (MIR) optical absorption increases with crystallinity and spectral shape depends on whether the melt depth during pulsed laser melting reaches interface between implanted layer and single-crystal silicon substrate or not. The MIR absorption intensity rapidly decreases with thermal annealing temperature and almost disappears at 750 °C. The activation energy of conductivity decreases with increasing laser fluence and further decreases with increasing post thermal-annealing temperature. The insulator-metal transition is observed for the sample annealed at 750 °C. These results indicate that there is no direct correlation between MIR optical absorption band and insulator-metal transition.